Testing a Structural Relationship Model of Perceived Organizational Support and Teamwork Skills in Teachers: The Mediating Role of School Collaborative Culture - Moosavinejad, Seyed Rohollah; Mohammadi Motlaq , Akbar (Assessment and Practice in Educational Sciences, 2025)
The purpose of this study was to examine the structural relationship model among perceived organizational support, school collaborative culture, and teamwork skills in high school teachers in Qom. Additionally, the mediating role of school collaborative culture in the relationship between organizational support and teamwork skills was assessed. The study sample consisted of 380 teachers in the field of educational sciences. Data were collected using the Teamwork Skills Questionnaire (Cumming et al., 2015), the Perceived Organizational Support Questionnaire (Rhoades & Eisenberger, 2002), and the Learning Community Culture Index (LCCI 4.0). Data analysis was conducted in two stages: descriptive and inferential. In the descriptive stage, mean, standard deviation, skewness, kurtosis, and correlation coefficients were calculated, and normality indices were examined using the Shapiro–Wilk and Kolmogorov–Smirnov tests. In the inferential stage, structural equation modeling (SEM) and model fit indices were applied. The findings showed that perceived organizational support had a direct and positive effect on teamwork skills, and school collaborative culture played a significant mediating role in this relationship. The results indicate that strengthening organizational support and fostering a collaborative school culture can enhance teachers’ teamwork skills and contribute to improving schools’ collective performance